Legal Protection for Children in Conflict with the Law Through the Diversion as a Tool of Social Engineering - Allen Ersandy Harindinata (Wiraraja University, 2024)
The purpose of this study is to examine and analyze the principle of protection for children who commit crimes from the perspective of National law in Indonesia. Children based on physical, mental and social development have a weak position compared to adults, so that children who commit delinquency need to be handled specially. Therefore, the treatment of delinquent children should be different from the treatment of adults. Handling of children in conflict with the law must be based on the best interest of the child . The research method used is the normative legal research method using a legislative approach and a conceptual approach. Based on the results of the study, the principle of protection for children in conflict with the law in the juvenile criminal justice system concerns substantial, structural and cultural issues. The law must be seen or viewed as a social institution that functions to meet social needs, so that law enforcers must treat children in conflict with the law differently from adult perpetrators. The 2012 SPPA Law has accommodated the principle of the best interest of the child with the existence of diversion based on the principle of restorative justice that prioritizes recovery between perpetrators, victims, witnesses and the community. The form of protection provided is about community involvement in preventing violence against children, the obligation of legal assistance during the trial process, the child's non-obligation to be detained during the trial process, rehabilitation to the process of reintegration into society after undergoing the criminal process.